Legislating for Equality A Multinational Collection of Non-Discrimination Norms. Volume IV: Asia and Oceania. - Naamat, Talia (BRILL, 2019)
Legislating for Equality - a Multinational Collection of Non-Discrimination Norms is a compilation of national constitutional provisions and laws on non-discrimination and the promotion of equality. The aim of the book, divided into four volumes, is to provide a comprehensive overview of the legal frameworks of all UN Member States on matters relating to discrimination on the basis of race, religion and ethnicity, prohibition of hate crimes and "hate speech". Each volume also includes relevant international and regional treaties and ratification tables. The first volume on Europe was published in August 2012. The second volume on the Americas was published in 2013, and the third volume on Africa was published in 2016. In this final volume of the series, we turn our attention to Asia and Oceania.